Optimization of Graphite-ZnO-Based Conductive Ink Formulation with PVP-Chitosan Polymer Matrix for Printed Electrodes on Textile Substrates: Evaluation of Electrical Stability and Mechanical Durability - Bintan Oktaviani; Hendra (JST (Jurnal Sains dan Teknologi), 2026)
The development of wearable biosensors is hampered by the limited availability of mechanically stable, economical, and environmentally friendly conductive inks. Precious metal-based inks are expensive and unsustainable, while graphite inks often peel off from textiles due to poor adhesion and uneven particle distribution. Although PVP and chitosan have the potential to improve coating stability, their optimal combination has not been widely studied, especially in graphite-ZnO blend systems. This study aimed to optimize graphite-ZnO-based conductive ink formulations using a PVP-Chitosan polymer matrix for printed electrodes on textile substrates, including evaluation of electrical stability and mechanical durability. This study fills this gap by optimizing graphite-ZnO-based conductive ink formulations with PVP-chitosan matrix through screen printing on cotton fabric. Six compositions were tested for viscosity, printed, and then evaluated through bending (100 cycles), immersion (3 cycles), and washing (ISO 105-C06:2010) tests. Resistance was measured with a two-point probe multimeter and analyzed using multiple regression. Sample S6 (37% graphite, 10% ZnO, 8% PVP, 5% chitosan, 40% ethanol) showed the best stability: resistance changes of 95.32% (bending), 6.6% (immersion), and -60.06% (washing). PVP proved to be the most effective in enhancing coating resistance. This formulation is worthy of being developed as a flexible electrode for wearable biosensors.